Closing the global radiocarbon budget 1945 - 2005 - Naegler, Tobias; Levin, Ingeborg (Universitätsbibliothek der Universität Heidelberg, 2006)
The global radiocarbon cycle of the last 60 years was simulated with the Global RAdioCarbon Exploration Model (GRACE). The total radiocarbon production by atmospheric nuclear bomb tests was determined using available stratospheric and tropospheric radiocarbon (14C) observations as constraints. To estimate the range of uncertainty in the explosive force of atmospheric nuclear bomb tests and their respective 14C yield factor, we applied different published bomb test compilations. Furthermore, to account for a possible small bias in the available stratospheric excess radiocarbon observations, we tested the different bomb test compilations with both uncorrected and corrected stratospheric 14C observations. For each of these scenarios of the total bomb 14C burden, the model simulated the distribution of excess radiocarbon among the stratosphere, troposphere, biosphere, and ocean carbon reservoirs. With a global bomb 14C production of 598—632*10^26 atoms (99-105 kmol) 14C between 1945 and 1980, simulated excess radiocarbon inventories are in good agreement with all available stratospheric and tropospheric radiocarbon observations as well as with the latest estimates of the ocean excess radiocarbon inventories during the GEOSECS and WOCE surveys from Peacock (2004) and Key et al. (2004). For the very first time, our model is thus capable of closing the excess radiocarbon budget on the basis of our current knowledge of exchange rates and reservoir sizes in the global carbon system.